Understanding the delivery of Islamophobic hate speech via social media in Indonesia - Kastolani Kastolani (Indonesian Journal of Islam and Muslim Societies, 2020)
Various prior studies on Islamophobia had largely utilized Western perspectives.This occurred on account of Islam and Muslims being a minority group that is considered as a threat to the majority. This article discusses the delivery of Islamophobic hate speech via social media in the context of Indonesia, where the majority of the population are Muslims. This study found that the delivery of hate speech concerning via social media in the Indonesian context can be understood in three different manners, namely: First, Islamophobia is a reaction to religious sermons delivered by Muslim pundits discrediting other religions, particularly the Christian faith. Second, Islamophobia is a form of freedom of expression for netizens in Indonesia’s current democratic climate. Third, Islamophobia is a form of identity politics for netizens on social media due to the impact of religious based political polarization. Subsequently, this study contributes a new understanding of Islamophobia within the context of Muslims as the majority and of netizens’ activities on social media in Indonesia. The research data were obtained by observing Facebook, Instagram, YouTube, and Twitter timelines containing Islamophobic hate speech that had gone viral on social media. Berbagai penelitian sebelumnya tentang Islamophobia sebagian besar telah memanfaatkan perspektif Barat. Artikel ini mendiskusikan penyampaian ujaran kebencian Islamophobia melalui media sosial dalam konteks Indonesia sebagai negara yang mayoritas penduduknya penganut agama Islam (muslim). Penelitian ini menemukan bahwa penyampaian ujaran kebencian tentang Islamophobia melalui media sosial dalam konteks Indonesia dapat dibaca sebagai tiga hal, yaitu: Pertama, Islamophobia merupakan reaksi terhadap ceramah keagamaan dari kalangan agamawan muslim yang mendiskreditkan agama lain, terutama keyakinan agama Kristen. Kedua, Islamophobia merupakan bentuk kebebasan berekspresi bagi netizen dalam iklim demokrasi di Indonesia saat ini. Ketiga, Islamophobia merupakan bentuk politik identitas netizen di media sosial karena dampak polarisasi politik berbasis keagamaan. Sehingga, penelitian ini berkontribusi terhadap pemahaman baru tentang Islamophobia dalam konteks muslim sebagai mayoritas dan aktivitas netizen di media sosial di Indonesia. Data penelitian diperoleh dari pengamatan terhadap media social seperti facebook, Instagram, YouTube dan Twitter yang memuat ujaran kebencian tentang Islamophobia yang viral di media social.